Efficacy of the Li maneuver in treating posterior canal benign paroxysmal positional vertigo. (3rd June 2017) - Li, Jinrang; Tian, Shiyu; Zou, Shizhen
Abstract: Conclusion: The Li maneuver is a safe, effective, and simple repositioning method for the treatment of BPPV. It is simple to master and exerts an exact effect. As a rapid repositioning method, the Li maneuver can result in reduced treatment times and increased treatment efficacy, and is, therefore, especially suitable for patients with limited cervical spine movement. Objective: To compare the short-term efficacies of the Li and Epley maneuvers in treating posterior canal benign paroxysmal positional vertigo (PC-BPPV). Methods: A total of 120 patients with PC-BPPV were randomly treated by either the Li or Epley maneuvers at our department between May 5, 2014 and July 30, 2015. Follow-up examinations were performed 3 days and 1 week after the first repositioning. Results: Of the 120 patients initially enrolled, 113 (72 females; 41 males; average age = 52 years; Li and Epley maneuver groups, 56 and 57 cases, respectively) satisfied the inclusion and exclusion criteria of this study. There were no statistically significant differences between the two groups of patients in terms of the success rates of treatment at either the 3-day or 1-week follow-ups ( p = .756 and .520, respectively).